EFFECT OF VISUAL ART AND PICO GAME ON EVIDENCE-BASED PRACTICE COMPETENCY AMONG NURSING PROFESSIONAL PROGRAMME STUDENTS - Hasniatisari Haruni; Titis Kurniawan; Eka Afrima Sari; Nursiswati Nursiswati; Yusshy Kurnia Heliani (INDONESIAN NURSING JOURNAL OF EDUCATION AND CLINIC (INJEC), 2025)
Introduction Most nursing students in Indonesia require specialized competency training to implement evidence-based practice (EBP) in the clinical setting. Some literature revealed that art and game-based learning methods can improve students' skills and self-efficacy on the topics studied. Therefore, this study was conducted to evaluate the application of visual art plus the PICO game in improving EBP competence in nursing students.Methods: This study used a quantitative experimental design with a pretest-posttest one-group design approach. The study was conducted on 50 students at one of the nursing education institutions in Bandung, West Java, Indonesia, with a purposive sampling technique. The visual art plus PICO game intervention was given for 25 minutes by implementing drawing activities and card games. The EBP questionnaire consisting of eight questions was used as a research instrument to obtain data on students' EBP competence at the pretest and posttest. Demographic data was analyzed by descriptive statistical analysis, and the difference in EBP competence between the pretest and posttest was analyzed by independent t-test.Results: The data analysis results showed a significant difference in students' EBP competence before and after being given the visual art plus PICO game intervention (p<0.00). The mean score of students' EBP competence increased from 38.22 in the pretest to 41.56 in the posttest. Gender, grade point average, and learning style of students also influenced the results obtained in this study.Conclusion: Visual art and PICO game interventions were effective learning methods to improve students' EBP competence. Visual art plus the PICO game can be one of the options for learning methods to improve students' EBP competence.